2017
DOI: 10.1257/aer.20151404
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and Spurring High-Growth Entrepreneurship: Experimental Evidence from a Business Plan Competition

Abstract: Almost all firms in developing countries

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
108
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(117 citation statements)
references
References 32 publications
2
108
2
5
Order By: Relevance
“…It is also critical for the creation of better quality jobs. While there remains some debate on which types of firms create the most jobs-microenterprises versus large establishments, newly created versus old enterprises-the literature has come to some consensus on the importance of young, dynamic, high-growth enterprises (sometimes referred to as "gazelles"), even if there is no agreement on how to identify these firms ex ante (see Audretsch 1995;Dwyer and Kotey 2016;McKenzie 2015). However, there is little debate that productivity enhancement of firms, of all ages and sizes, matters greatly for the delivery of sustainable, quality jobs.…”
Section: Enterprise Transformation and Productivitymentioning
confidence: 99%
“…It is also critical for the creation of better quality jobs. While there remains some debate on which types of firms create the most jobs-microenterprises versus large establishments, newly created versus old enterprises-the literature has come to some consensus on the importance of young, dynamic, high-growth enterprises (sometimes referred to as "gazelles"), even if there is no agreement on how to identify these firms ex ante (see Audretsch 1995;Dwyer and Kotey 2016;McKenzie 2015). However, there is little debate that productivity enhancement of firms, of all ages and sizes, matters greatly for the delivery of sustainable, quality jobs.…”
Section: Enterprise Transformation and Productivitymentioning
confidence: 99%
“…See Klinger and Schundeln (2011) for analysis of a similar competition run by Technoserve in three Central American countries. McKenzie (2015) reports on the results of a business plan competition in Nigeria while Fafchamps and Quinn (2015) report on a business plan competition in Ethiopia, Tanzania and Zambia.…”
Section: Jel Codes: L26 O12 O31mentioning
confidence: 99%
“…The winners were given a substantial amount of moneyon average US$50,000-to implement their business plans. Three years after the implementation, a follow-up survey of these businesses showed that the programme had been successful in helping the winning firms to achieve higher survival rates, acquire more capital and employ more workers (McKenzie 2015). MSME-financing programmes in Tanzania, on the other hand, make no attempt to screen firms for their growth potential.…”
Section: Targeting the In-between Sectormentioning
confidence: 99%